109k views
17 votes
Can someone help me understand how to solve this problem?

Can someone help me understand how to solve this problem?-example-1
User Fanor
by
6.3k points

1 Answer

10 votes

Answer:

Explanation:

Multiply both sides of the equation by 10:

9x²+7x-2=0

Write 7x as a difference:

9x²+ 9x-2x -2 =0

Factor the expression:

9x x (x+1)-2x-2 = 0

9x x (x+1) - 2 (x+1) =0

Then seperate them into possible cases:

(x+1) x (9x-2) = 0

x+1 = 0

9x - 2= 0

The equation has 2 solutions:

x1 = -1

x2 =
(2)/(9)

User Hdost
by
6.5k points